Thalidomide in combination with vincristine, epirubicin and dexamethasone (VED) for previously untreated patients with multiple myeloma. - Schütt, P; Ebeling, P; Buttkereit, U; Brandhorst, D; Opalka, B; Hoiczyk, M; Flasshove, M; Hense, J; Bojko, P; Metz, K; Moritz, T; Seeber, S; et al. (2005)
The present study aimed to evaluate the side-effects and efficacy of thalidomide in combination with an anthracycline-containing chemotherapy regimen in previously untreated myeloma patients. Thalidomide (400 mg/d) was combined with bolus injections of vincristine and epirubicin and oral dexamethasone (VED). Chemotherapy cycles were repeated every 3 wk until no further reduction in myeloma protein was observed, whereas the treatment with thalidomide was continued until disease progression. Thirty-one patients were enrolled, 12 patients were exclusively treated with thalidomide in combination with VED and 19 patients additionally received high-dose melphalan, for consolidation. Adverse events and response to therapy were assessed prior to treatment with high-dose chemotherapy. Response to thalidomide combined with VED was complete remission in six patients (19%), partial remission in 19 patients (61%), stable disease in five patients (16%), and progressive disease in one patient (3.2%). Grade 3 and 4 adverse events consisted of leukocytopenia in 10 patients (32%), and thrombocytopenia and anemia in one patient each (3.2%). Neutropenic infections grade 3 and 4 occurred in seven (23%) and three patients (9.7%), respectively, including two patients (6.5%) who died from septic shock. Deep vein thrombosis occurred in eight patients (26%), constipation in 20 patients (65%), and polyneuropathy in 20 patients (65%). The probability of event-free survival and overall survival in the whole group of patients at 36 months were 26 and 62%, respectively. In conclusion, the combination of thalidomide with VED appears to be highly effective in previously untreated patients with multiple myeloma, but it is associated with a high rate of thrombotic events, polyneuropathy, and neutropenic infections.